Extended-Spectrum β-Lactamase (ESBL) Genotypes among Multidrug-Resistant Uropathogenic Escherichia coli Clinical Isolates from a Teaching Hospital of Nepal. (15th April 2020) - Pandit, Roshan; Awal, Balkrishna; Shrestha, Sumesh Shreekhanda; Joshi, Govardhan; Rijal, Basista Prasad; Parajuli, Narayan Prasad
Abstract : Urinary tract infections (UTI) represent the most common bacterial infections among patients visiting outpatient clinics of healthcare centers in Nepal. However, treatment of such infections is compounded by emergence and spread of multidrug-resistant uropathogens associated with extended-spectrum β -lactamases (ESBLs). In this study, we aimed to investigate the burden of antimicrobial resistance and occurrence of ESBL genes among clinical isolates of uropathogenic Escherichia coli at a tertiary care teaching hospital of Nepal. During the study period, we processed a total of 1, 626 urinary tract specimens, isolated significant bacterial pathogens, and investigated their antimicrobial susceptibilities. Escherichia coli ( n = 154), the predominant pathogen associated with UTI, was further investigated for the existence of ESBL enzymes by using conventional phenotypic as well as molecular approaches. Among suspected cases of UTI, we found that 15.2% were having UTI and female patients of the reproductive age group were more affected (p < 0.05 ). Escherichia coli (154, 62.1%) was the key uropathogen, and majority (∼64.9%) of them were multidrug resistant (MDR). Among MDR E. coli isolates, 40.3% were producing extended-spectrum β -lactamases (ESBLs). bla-TEM (83.8%), bla-CTX-M (66.1%), and bla-SHV (4.8%) were common ESBL genotypes. Nitrofurantoin, gentamycin, and imipenem were the most effective antibiotics for ESBL-producing Escherichia coli isolates. It indicates that the high rates of multidrug-resistant Escherichia coli are frequent causes of UTI in our hospital. Nitrofurantoin and aminoglycosides are the most useful first-line drugs to be used in the cases of UTI. We recommend the regular investigation of drug resistance among all isolates and develop a useful antibiotic prescription policy in our country.